Efek Mutu Pelayanan Terhadap Kepuasan Pasien Rawat Jalan Poliklinik Umum Di Puskesmas Baki Tahun 2017 - Bangkit Ary Pratama (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2018)
Based on the preliminary survei results showed that out of 10 questionnaire questionnaires given to respondents, 6 respondents considered lack of discipline, politeness and friendliness in service delivery, 2 other respondents considered inadequate facilities in the service and 2 respondents considered lacking in service timeliness, it is necessary to research the quality of services provided to patients, because patient satisfaction is one indicator of the success of health services. The purpose of this research is to know the relation of quality of outpatient health service at Baki Sukoharjo Public Health Center. This research uses descriptive analytic research with research design using cross-sectional approach. Method of collecting data with questionnaire, population is recapitulation of outpatient visit that register general pol at Tras Health Center Year 2017 and number of sample of research are 56 outpatient. Data analysis used is univariate analysis and bivariate analyst. Sampling by accidental sampling (people encountered at the same time).Statistical test using spearman's rho correlation. Based on the results of research that has been done by the author at Baki Sukoharjo Health Center shows that the hypothesis is accepted that there is a positive and significant relationship between the quality of health services with the level of outpatient satisfaction at Baki Sukoharjo Public Health Center, with p value= 0.001 with the value (r) of 0.802 means included in the interval very strong correlation strength. The conclusion of this study is there is a significant relationship between the quality of health services with the level of patient satisfaction in Baki Sukoharjo Health Center with a very strong correlation strength.